2016
DOI: 10.1186/s13068-016-0534-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep metagenome and metatranscriptome analyses of microbial communities affiliated with an industrial biogas fermenter, a cow rumen, and elephant feces reveal major differences in carbohydrate hydrolysis strategies

Abstract: BackgroundThe diverse microbial communities in agricultural biogas fermenters are assumed to be well adapted for the anaerobic transformation of plant biomass to methane. Compared to natural systems, biogas reactors are limited in their hydrolytic potential. The reasons for this are not understood.ResultsIn this paper, we show that a typical industrial biogas reactor fed with maize silage, cow manure, and chicken manure has relatively lower hydrolysis rates compared to feces samples from herbivores. We provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
92
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 70 publications
12
92
1
1
Order By: Relevance
“…They are known as typical colonizers of biogas plants and competitors in the anaerobic degradation of organic material. The ratio of Firmicutes versus Bacteroidetes was in the range of 1.7:1 and 6.1:1, which is comparable to previously described observations in biogas plants (Güllert et al ., ). In other plant biomass degrading habitats, like cow rumen or elephant intestine, significantly lower ratios of Firmicutes versus Bacteroidetes are typically observed as part of the healthy gut flora (Güllert et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…They are known as typical colonizers of biogas plants and competitors in the anaerobic degradation of organic material. The ratio of Firmicutes versus Bacteroidetes was in the range of 1.7:1 and 6.1:1, which is comparable to previously described observations in biogas plants (Güllert et al ., ). In other plant biomass degrading habitats, like cow rumen or elephant intestine, significantly lower ratios of Firmicutes versus Bacteroidetes are typically observed as part of the healthy gut flora (Güllert et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The ratio of Firmicutes versus Bacteroidetes was in the range of 1.7:1 and 6.1:1, which is comparable to previously described observations in biogas plants (Güllert et al ., ). In other plant biomass degrading habitats, like cow rumen or elephant intestine, significantly lower ratios of Firmicutes versus Bacteroidetes are typically observed as part of the healthy gut flora (Güllert et al ., ). In the above‐mentioned habitats, as well as in the biogas reactor, Firmicutes and Bacteroidetes are involved in the degradation of biomass during the hydrolysis, acidogenesis and acetogenesis (Wirth et al ., ; Güllert et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The prevalence of Proteobacteria was also found in a sugarcane bagasse microbial community, although it has a much smaller proportion of Firmicutes [9]. The metagenomic and 16S rRNA amplicon data sets showed that microbial communities in biogas reactors were frequently affiliated with the phylum Firmicutes , which played a significant role in the anaerobic digestion process [12, 23, 24]. Like biogas reactors, the submerged fermentation under static culture conditions in this study provided a relatively anaerobic environment in favor of the growth of anaerobic bacteria such as Firmicutes .…”
Section: Resultsmentioning
confidence: 99%